DAMPAK RESTRUKTURISASI PADA KINERJA PERUSAHAAN - Efriyenti, Dian; Prima, Argo Putra; Mulawarman, Mulawarman; Yusuf, Muhammad (LPPM Universitas Putera Batam, 2025)
The case of PT Lippo's financial report manipulation is clear evidence that accounting fraud can still occur due to weak oversight by the board of commissioners. This situation even forced the government to intervene and provide assistance. This phenomenon demonstrates the weak implementation of Good Corporate Governance (GCG), where managers' personal interests prevail over the company's interests. Furthermore, company size also influences earnings management practices. Small companies more often engage in earnings management to present a superior performance to attract investors. Meanwhile, large companies are typically better able to manage risks, including political risks, allowing them to focus more on maximizing profits to strengthen the ecosystem. This study aims to examine how company size and GCG influence earnings management practices, both separately and jointly. The results of the study, conducted on 48 listed mining companies, found that company size and GCG significantly influence earnings management practices. This means that good governance and proportional company management are crucial for mitigating the risk of financial report manipulation.